PERANCANGAN APLIKASI PENCARIAN FASILITAS OLAHRAGA DAN PARTNER OLAHRAGA BERBASIS WEB - Puti Andam Suri (University of Muhammadiyah Tangerang, 2022)
The lack of information about sports facilities occurs and obstructs many people to exercise, especially, for the types of sports that most people are unfamiliar with or rarely interested in. The purpose of this research is to make an application that aims to help people find sports partners/ community and facilities in the sports they are interested in, provide the public with information about partner or community, facilities locations, events, sports news, and threads that can share information and experience in it. This application is a web-based application where it developed using object-oriented analysis and design concepts. Also, this application conducts the waterfall life cycle model for the application development process.